2003
DOI: 10.1099/vir.0.19270-0
|View full text |Cite
|
Sign up to set email alerts
|

Autographa californica nucleopolyhedrovirus infection of Spodoptera frugiperda cells: a global analysis of host gene regulation during infection, using a differential display approach

Abstract: Autographa californica nucleopolyhedrovirus (AcMNPV), the type member of the virus family Baculoviridae, infects pest insects and has been the subject of many studies for its development as a biopesticide. It is also the virus upon which most of the commercial baculovirus protein expression systems are based. AcMNPV infection of cultured host Spodoptera frugiperda (Sf9) cells can induce a number of alterations of host cell properties including altering the cellular cytoskeleton, an arrest of the cell cycle in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 46 publications
5
68
1
3
Order By: Relevance
“…Furthermore, it is known that baculoviral infection is associated with global shutdown of host protein synthesis at 12-18 h p.i., the mechanism of which is still unknown (Nobiron et al, 2003;Ooi & Miller, 1988;Tjia et al, 1979). It is interesting to note that most of the baculoviral miRNAs in our deep-sequencing analysis also start to appear by 12 h p.i.…”
Section: Expression Profiling Of Spltnpv Mirnas At Different Time Intmentioning
confidence: 99%
“…Furthermore, it is known that baculoviral infection is associated with global shutdown of host protein synthesis at 12-18 h p.i., the mechanism of which is still unknown (Nobiron et al, 2003;Ooi & Miller, 1988;Tjia et al, 1979). It is interesting to note that most of the baculoviral miRNAs in our deep-sequencing analysis also start to appear by 12 h p.i.…”
Section: Expression Profiling Of Spltnpv Mirnas At Different Time Intmentioning
confidence: 99%
“…To date, we are unaware of any structural evidence that LacDiNAc has been found in the N-glycans of any recombinant glycoprotein produced in baculovirus-infected T. ni cells or larvae. In fact, considering that the expression of most or all host cell genes is repressed during baculovirus infection (96), and that ␤4-Nacetylgalactosaminyltransferase activity is dramatically reduced during baculovirus infection (30), it seems rather unlikely that LacDiNAc will occur in recombinant N-glycoproteins produced using the baculovirus expression system. It is interesting to consider in retrospect that we actually intended to isolate an insect ␤4-galactosyltransferase cDNA in this study.…”
Section: Cloning and Functional Analysis Of Tn␤4galnact 33515mentioning
confidence: 99%
“…Given that the heat shock cognate protein gene (hsc70) is the only gene that has been sequenced among the HSP/HSC70 family in S. frugiperda cells [24], and that it has been found to be transiently up-regulated during baculovirus infection [24,25], we chose hsc70 as a representative of the heat shock response in S. frugiperda cells. Transcripts from the infected cells were collected at 0, 2, 4, 6, 8 hpi and quantified by RT-qPCR.…”
Section: The Interplay Between Hsc70 and Ie2 During Baculovirus Infecmentioning
confidence: 99%
“…We found that heat shock proteins (HSPs) are one of the major components that complex with the IE2 protein. Stimulation of a heat shock response during baculovirus infection and its importance for virus amplification has been frequently mentioned in the literature [23][24][25][26]. However, the viral factors that are responsible for this effect and the mechanism underlying the interaction between viral factors and HSPs are still unclear [27].…”
Section: Introductionmentioning
confidence: 99%